Overcoming the unprecedented: Micro, small and medium hospitality enterprises under COVID-19. (May 2022) - Alonso, Abel Duarte; Bressan, Alessandro; Kok, Seng Kiat; Sakellarios, Nikolaos; Thi Kim Vu, Oanh; O'Shea, Michelle; Koresis, Alex; Solis, Maria Alejandra Buitrago; Santoni, Leonardo J.
Abstract: The sudden irruption of COVID-19 has paralysed, even devastated, numerous industries. Academic and industry publications also convey the destructive impacts of this phenomenon on hospitality and tourism businesses. While business owners and managers are still constrained by unpredictability, restrictions, and ongoing uncertainty, those vying to continue will need to build their adaptive skill repertoire to cope with the crisis-related regime. This study is primarily concerned with businesses' adaptation phase from owners/managers' viewpoints, including how they manage and envision a future coexistence with COVID-19 threats. Drawing on an international sample of owners/managers of hospitality and tourism businesses, and considering the foundations of the dynamic capabilities framework, eight dimensions emerged from the findings. Five of these, persevering, dynamic, austere restrictions, business environment, and stakeholder, strongly suggest the relevance of reconfiguring, a cluster of dynamic capabilities. Together, the dimensions demonstrate participants' strong commitment to navigate through the threat while pursuing socioeconomic sustainability. Highlights: Investigates adaptation strategies to respond to the COVID-19 threat. Focuses on micro, small and medium tourism and hospitality firms. Proposes a multidimensional framework based upon emerging dimensions. Extends theoretical underpinnings of the dynamic capabilities framework. Provides practical and theoretical dimensions to understand adaptation to COVID-19.